Development of e-Student Worksheets Based on Multiple Representations of Factors Affecting Reaction Rates - Farah Meutia; Nurdin Nurdin; Sri Winarni (Postgraduate, University of Mataram, 2021)
The research had been carried out to develop the e-student worksheet (e-SW) based on multiple representational learning models on the material factors which affect the rate of reaction to determine its effectiveness in understanding the concepts and activities of students, as well as the teacher’s and the student’s responses towards e-worksheet application. The research method and development (R&D) of the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model were used for the development of e-SW. The research samples used were the students of class XI MIPA 1, and the chemistry teachers of class XI of senior high school 3 Banda Aceh, then the determination of the sample for implementation was carried out using random sampling techniques. Based on the results of the study, it can be concluded that an e-worksheet based on the developed multiple representation learning models on the factors which affect the reaction rate fulfilled the very feasible criteria with the acquisition of validity and reliability of 0.85 and 85. Complete understanding of the concepts and activities of students using e-worksheet was splendid, namely 84.8 and 85%. The response of students and teachers to the development of e-worksheet based on the multiple representation learning models was also splendid